Adat Space in Muslim-Christian Conflict Resolution at Minang Realm, West Sumatera, Indonesia - Andri Ashadi; Sefriyono Sefriyono; Ade Irwansyah (UIN Sunan Gunung Djati, 2022)
Adat or custom, which was recommended as an ethnic and religious platforms reconciliation of post-violence in Eastern part of Indonesia, has become a resolution to the occurred conflict; hence, it does not lead to violence between the MM and NK communities in Nagari Sungai Buluh, Padang Pariaman, West Sumatra. Adat has encouraged the conflicting parties to find the root of causes and to formulate various approved settlement models. The purpose of this research is to prove that adat has been used in formulating various resolution models according to the types of conflicts that occur. The research data comes primarily from various documents belonging to the nagari which are strengthened by interviews with the parties involved in conflict resolution. The thematic mapping of the documents was confirmed and explored through interviews with participants from both the MM and NK communities. The results of the study revealed that the conflict resolution model offered by adat ranges from prohibitions and restrictions on raising pigs to a total ban but provides a number of payments and replaces them with ducks. Deliberation, consensus and mediation, which are the main mechanisms of adat in conflict resolution, have become guarantees and protection for minority communities. In line with that, the article suggests the need for synergy with religious values; hence, the function of the religious values is more significant in resolving religious conflicts that occur between the majority and minority communities. The space for social conflict, religious conflict and even customary conflict itself is increasingly open in the future along with the strengthening of conservatism both on a local, national and global scale so that various models of conflict resolution are needed, including custom-based ones.